Thrombectomy of an Acute Ischemic Stroke in a Child with COVID-19 and MIS-C: Case Analysis and Literature Context - Paul R. Carney; Dakota W. Stevenson; Edith Riggs; Matilda Dervisevic; Constanza X. Carney; Camilo R. Gomez (MDPI AG, 2023)
We describe a very young child who developed an acute ischemic stroke from a LAO, while affected by COVID-19 and MIS-C, and whom we treated successfully with thrombectomy. We compare his clinical and imaging findings with those of the existing case reports, and we explore the multifactorial nature of such a neurovascular complication, particularly in the context of the most recent publications regarding the multifactorial endothelial derangements produced by the illness.